84.1k views
2 votes
3x + 2y = -9
4x - 2y = -26
please help I have to solve this with the elimination method

User Guilleva
by
5.9k points

1 Answer

3 votes

Answer:

x = - 5, y = 3

Explanation:

Given the 2 equations

3x + 2y = - 9 → (1)

4x - 2y = - 26 → (2)

Adding (1) and (2) term by term eliminates the y- term, that is

7x = - 35 ( divide both sides by 7 )

x = - 5

Substitute x = - 5 into either of the 2 equations and solve for y

Substituting into (1)

3(- 5) + 2y = - 9

- 15 + 2y = - 9 ( add 15 to both sides )

2y = 6 ( divide both sides by 2 )

y = 3

User Ovidiu Cristescu
by
5.8k points